2016
DOI: 10.1158/1940-6207.capr-15-0434
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Osteopontin and Prediction of Hepatocellular Carcinoma Development in a Large European Population

Abstract: We previously identified osteopontin (OPN) as a promising marker for the early detection of hepatocellular carcinoma (HCC). In this study, we investigated the association between pre-diagnostic circulating OPN levels and HCC incidence in a large population-based cohort. A nested-case control study was conducted within the EPIC cohort. During a mean follow-up of 4.8 years, 100 HCC cases were identified. Each case was matched to two controls and OPN levels were measured in baseline plasma samples. Viral hepatiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…OPN is involved in cell migration and inflammatory signaling, and previous studies have demonstrated that OPN was associated with hepatic inflammation and invasiveness in hepatocellular carcinoma (HCC) (8,9,21). In line with these experimental observations, an association of circulating OPN levels and HCC incidence has previously been demonstrated in a population cohort of more than 520,000 subjects from ten Western European countries (21).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…OPN is involved in cell migration and inflammatory signaling, and previous studies have demonstrated that OPN was associated with hepatic inflammation and invasiveness in hepatocellular carcinoma (HCC) (8,9,21). In line with these experimental observations, an association of circulating OPN levels and HCC incidence has previously been demonstrated in a population cohort of more than 520,000 subjects from ten Western European countries (21).…”
Section: Discussionsupporting
confidence: 53%
“…In line with these experimental observations, an association of circulating OPN levels and HCC incidence has previously been demonstrated in a population cohort of more than 520,000 subjects from ten Western European countries (21). As cell proliferation is among the key mechanisms in HCC and liver repair (8,(22)(23)(24), high levels of OPN may suggest tumor progression or liver regeneration.…”
Section: Discussionmentioning
confidence: 58%
“…These include the following markers: epithelial cell adhesion molecule, osteopontin, surface marker vimentin, transforming growth factor beta/sirtuin, and DNA repair pathway members. These novel biomarkers reflect biological significance in HCC …”
Section: Surveillancementioning
confidence: 99%
“…Other emerging biomarkers include osteopontin (OPN) [8183], latent TGF-beta binding protein I (LTBP1) [84], latent TGF-beta binding protein II (LTBP2) [83], DKK1 [85], midkine (MDK) [86, 87], GP73 [88, 89], glypican 3 (GPC3) [90], and a variety of miRNAs [91, 92]. These markers are under active investigation and none of them have been approved for clinical use.…”
Section: Emerging Biomarkers Not Yet In Clinical Usementioning
confidence: 99%